Validation of the Spanish Version of the Massachusetts General Hospital-Sexual Functioning Questionnaire (MGH-SFQ) with Sexual Arousal Measures in Men - Juan Carlos Sierra; Ana I. Arcos-Romero; Reina Granados; Oscar Cervilla; Pablo Mangas; Laura Elvira Muñoz-García; Ana Álvarez-Muelas (International Journal of Psychological Research, 2023)
Objective. Provide new validity evidence of the Spanish version of the Massachusetts General Hospital-Sexual Functioning Questionnaire (MGH-SFQ) by associating its scores with measures of sexual arousal. Method. In a sample of 48 men, using a quasi-experimental design, sexual functioning, propensity for sexual inhibition/excitation, subjective sexual arousal, and genital response (penile plethysmography recorded with Biopac MP150 equipment) were evaluated. Results. Arousal and erection scores correlated with sexual inhibition due to the threat of performance failure (r = −.29; p < .05) and genital response (r = .31; p < .05), respectively. Participants with difficulties in sexual functioning indicated greater sexual inhibition due to the threat of performance failure (p = .04) and lower intensity in their genital response (p = .05). Conclusions. The validity of the measures obtained with the Spanish version of the MGH-SFQ is supported, showing the erection item to be useful for the detection of possible erectile disorders.